A ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN VALUE FOR MONEY PADA DINAS SOSIAL KABUPATEN TAPANULI SELATAN: ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN VALUE FOR MONEY PADA DINAS SOSIAL KABUPATEN TAPANULI SELATAN - Alviana Sahrini Nasution; Fauzi Arif Lubis; Rahmat Daim Harahap (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
Finance at the Social Service of the South Tapanuli Regency in the Institutional Empowerment and Social Welfare Program in 2019-2021 using the Value for Money concept. The research method used in this research is descriptive qualitative method. Sources of data used are primary data and secondary data. Data collection techniques used are observation/observation, interviews and documentation. The Value for Money approach is seen from three aspects, namely the economic level, the efficiency level and the level of effectiveness. Measurement of economic value is based on a comparison of the budget with budget realization. The measurement of efficiency value is based on a comparison of output and input, where the output is obtained from the performance achievements of the South Tapanuli Regency Social Service. While the value of effectiveness is based on a comparison of outcomes with outputs, where outcomes are targets to be achieved, while outputs are performance achievements of the South Tapanuli Regency Social Service. The results of this study indicate that the financial performance of the Social Services Office of South Tapanuli Regency in the Institutional Empowerment and Social Welfare Program in 2019-2021 in terms of the economic level, namely 71.66% is in the fairly economical category, 89.40% is included in the economic category and 97 .77% fall into the very economical category. Judging from the level of efficiency that is equal to 97.68%, 91.72% and 94.09% fall into the very efficient category. Judging from the level of effectiveness, namely 70% is included in the quite effective category, 82% is included in the effective category and 92% is included in the very effective category.